Clinical Value of Amide Proton Transfer-weighted Imaging in Ischemic Stroke: A Comparative Study with Apparent Diffusion Coefficient and CT Perfusion - Le Zhou; Renjun Huang; Hui Wang; Mengying Zhu; Xiaofei Zhou; Yi Zhang; Xinbing Zheng; Yonggang Li (Current Medical Imaging Formerly Current Medical Imaging Reviews, 2026)
Introduction: Diffusion- and perfusion-based imaging, including Apparent Diffusion Coefficient (ADC) and CT Perfusion (CTP), are standard tools for evaluating ischemic stroke but primarily reflect structural and hemodynamic changes. They provide limited insight into tissue metabolism. Amide Proton Transfer-weighted (APTw) imaging enables noninvasive assessment of pH-related metabolic alterations and may offer complementary diagnostic and prognostic information. Materials and Methods: In this prospective study, 54 patients with hyperacute or acute ischemic stroke (mean age 64.39 ± 10.91 years; 41 males) were enrolled. Correlations between APTw and conventional imaging parameters, including ADC, Cerebral Blood Volume (CBV), Cerebral Blood Flow (CBF), and Time to Peak (TTP), were analyzed. Kaplan–Meier analysis assessed 18-month outcomes. Time-dependent Receiver Operating Characteristic (ROC) analysis, decision curve analysis (DCA), calibration curves, and Clinical Impact Curves (CIC) were used to evaluate prognostic performance. Results: APTw values were significantly correlated with CBV (r = 0.6886), CBF (r = 0.6702), ADC (r = 0.6565), and TTP (r = –0.6519) (all p < 0.05). Kaplan–Meier analysis demonstrated significant differences in 18-month outcomes between APTw-based subgroups (log-rank p < 0.05). APTw achieved higher AUCs at 6, 12, and 18 months (0.821, 0.831, and 0.877) than ADC and CTP parameters. DCA, calibration, and CIC analyses confirmed stable predictive performance. Discussion: APTw showed strong concordance with diffusion- and perfusion-based biomarkers while providing complementary metabolic information, suggesting exploratory comparative prognostic relevance in ischemic stroke. Conclusions: APTw imaging offers complementary metabolic insight and may enhance diagnostic and prognostic evaluation in ischemic stroke.